Cumulative mild head injury (CMHI) in contact sports:an evaluation of pre and post season cognitive profiles rugby players compared with non-contact sport controls at the University of Limpopo(Turfloop Campus) - Rapetsoa, Mokgadi Johanna (University of Limpopo, 2015)
The effect of Cumulative Mild Head Injury (CMHI) in contact sports, such as rugby, is seen increasingly at school level where more and more injuries are reported. Research on CMHI in contact sport is needed specifically amongst previously disadvantaged groups where little or no research has taken place. The research is thus intended to seek a better understanding of CMHI in the contact sport of rugby specifically amongst amateur players. A quantitative research approach was utilised with a quasi-experimental research design. A sample of 18 student rugby players and 18 volleyball (non-contact sport) controls was used. In terms of mean performances the tests did not reveal a consistent pattern of deficits which is typically associated with the effects of Cumulative Mild Head Injuries. There were significant results however, in terms of variability that suggests potential deficits in attention among the rugby group. The results are therefore indicative of a poorer overall cognitive profile for the rugby playing group. It is concluded that the increased variability may be displayed in individuals who suffer CMHI at an earlier age.
Thesis (M.A.(Clinical Psychology)) -- University of Limpopo, 2015.
Keywords: Cumulative Mild Head Injury; Rugby Players; Non-Contact Sport Controls; Contact sports; Injuries; Clinical psychology